Correction: Microphase separation of highly amphiphilic, low N polymers by photoinduced copper-mediated polymerization, achieving sub-2 nm domains at half-pitch. Issue 7 (3rd February 2022) - Hancox, Ellis; Liarou, Evelina; Town, James S.; Jones, Glen R.; Layton, Siân A.; Huband, Steven; Greenall, Martin J.; Topham, Paul D.; Haddleton, David M.
Abstract : Correction for 'Microphase separation of highly amphiphilic, low N polymers by photoinduced copper-mediated polymerization, achieving sub-2 nm domains at half-pitch' by Ellis Hancox et al., Polym. Chem., 2019, 10, 6254–6259. DOI: ; 10.1039/c9py01312a .